EFFECTS OF ELEVATED ATMOSPHERIC CO2 CONCENTRATIONS ON CH4 AND N2O EMISSION FROM RICE SOIL: AN EXPERIMENT IN CONTROLLED-ENVIRONMENT CHAMBERS - Cheng W.; Yagi K.; Sakai H.; Kobayashi K. (My University, 2006)
The effects of elevated concentrations of atmospheric CO2 on CH4 and N2O emissions from rice soil were investigated in controlled-environment chambers using rice plants growing in pots. Elevated CO2 significantly increased CH4 emission by 58% compared with ambient CO2. The CH4 emitted by plant-mediated transport and ebullition–diffusion accounted for 86.7 and 13.3% of total emissions during the flooding period under ambient level, respectively; and for 88.1 and 11.9% of total emissions during the flooding period under elevated CO2 level, respectively. No CH4 was emitted from plant-free pots, suggesting that the main source of emitted CH4 was root exudates or autolysis products. Most N2O was emitted during the first 3 weeks after flooding and rice transplanting, probably through denitrification of NO3− contained in the experimental soil, and was not affected by the CO2 concentration. Pre-harvest drainage suppressed CH4 emission but did not cause much N2O emission (< 10 μg N m−2 h−1) from the rice-plant pots at both CO2 concentrations.
Keywords: DRAINAGE; ELEVATED CO2; METHANE; NITROUS OXIDE; RICE SOIL